Optimal Programming Problems for Crop Planning and Agricultural Resource Management - Paidipati, Kiran Kumar; Padi, Tirupathi Rao (Archives of Business Research, 2017)
*]:pointer-events-auto R6Vx5W_threadScrollVars scroll-mb-[calc(var(--scroll-root-safe-area-inset-bottom,0px)+var(--thread-response-height))] scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:86c961ff-1752-4d7b-a270-dd52769edfe9-5" data-turn-id-container="request-WEB:86c961ff-1752-4d7b-a270-dd52769edfe9-5" data-testid="conversation-turn-12" data-scroll-anchor="false" data-turn="assistant"><div class="text-base my-auto mx-auto pb-10 [--thread-content-margin:var(--thread-content-margin-xs,calc(var(--spacing)*4))] @w-sm/main:[--thread-content-margin:var(--thread-content-margin-sm,calc(var(--spacing)*6))] @w-lg/main:[--thread-content-margin:var(--thread-content-margin-lg,calc(var(--spacing)*16))] px-(--thread-content-margin)"><div class="[--thread-content-max-width:40rem] @w-lg/main:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="a2837abc-1e82-4d1c-a595-bde394c6238b" data-message-model-slug="gpt-5-3-mini" data-turn-start-message="true"> In this paper the researchers have developed two linear programming problems for optimal allocation of agricultural land with the objectives of minimizing farming costs and maximizing the revenue. The formulation of constraints is based on cost constraint of type of cultivation expenditure, allowable budget constraint for type of cultivation method, cost constraint with type of crop, allowable budget on the type of crop, total availability of land, competitive price of market on the price of each crop, minimum supporting price on each unit of crop, total investment and total revenue, breakeven yield of the crop, etc. The data on various categories are obtained through secondary data sources. Optimal sizes of agricultural land for each crop are obtained after solving all the combinations of programming problems. The decision-making policies are suggested after analyzing the outputs on the parameters for management of agricultural resources.